2015
DOI: 10.1016/j.neuron.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Hsc70-4 Deforms Membranes to Promote Synaptic Protein Turnover by Endosomal Microautophagy

Abstract: Synapses are often far from their cell bodies and must largely independently cope with dysfunctional proteins resulting from synaptic activity and stress. To identify membrane-associated machines that can engulf synaptic targets destined for degradation, we performed a large-scale in vitro liposome-based screen followed by functional studies. We identified a presynaptically enriched chaperone Hsc70-4 that bends membranes based on its ability to oligomerize. This activity promotes endosomal microautophagy and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 78 publications
7
136
0
1
Order By: Relevance
“…Late endosomes (LE) also contribute to selective degradation of cytosolic proteins targeted to this compartment by hsc70 through a process known as endosomal microautophagy (e‐MI) (Sahu et al ., 2011; Uytterhoeven et al ., 2015). Using the same N2a cells expressing WT, A152T, and P301L tau, we analyzed changes in cellular levels of these forms of tau upon disrupting e‐MI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Late endosomes (LE) also contribute to selective degradation of cytosolic proteins targeted to this compartment by hsc70 through a process known as endosomal microautophagy (e‐MI) (Sahu et al ., 2011; Uytterhoeven et al ., 2015). Using the same N2a cells expressing WT, A152T, and P301L tau, we analyzed changes in cellular levels of these forms of tau upon disrupting e‐MI.…”
Section: Resultsmentioning
confidence: 99%
“…2c). Therefore, we next analyzed possible changes in e‐MI activity in these cells using a reporter developed to study this pathway in flies and modified by our laboratory for use in mammalian cells (Uytterhoeven et al ., 2015). We transduced cells with the split mVenus plasmid containing the N‐terminal and C‐terminal of this protein tagged to the KFERQ motif (N‐KFERQ‐mVenus and C‐KFERQ‐mVenus).…”
Section: Resultsmentioning
confidence: 99%
“…This process, also recently identified in flies (38), is termed eMI to differentiate it from yeast microautophagy, which is also mediated by microvesicles but independently of ESCRT or hsc70. The current NMR and liposome binding assays pinpoint the lysine cluster (Lys-573, Lys-583, Lys-589, Lys-597, and Lys-601) as the major hsc-70/PS interaction site.…”
Section: Biological Role Of the Hsc-70-ps Complex In Cytosol-to-endosmentioning
confidence: 89%
“…Endosomal microautophagy is an ESCRT-dependent process, which is different from the ESCRT-dependent transport of ubiquitinated plasma membrane proteins into the endosomes, and relies on the cytosolic chaperone hsc-70 for the endosomal internalization of cytosolic proteins (8,38,39). Although hsc-70 can bind misfolded and ubiquitinated proteins, we previously demonstrated that in endosomal microautophagy, hsc-70 also binds proteins with KFERQ motifs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cytosolic proteins can also be selectively degraded by eMI after hsc70 binds in their sequence to the same pentapeptide motif previously described for CMA (Figure 4) (8). Hsc70 is not necessary for cargo targeting to microautophagy in yeast, but recent studies support occurrence of hsc70-mediated eMI in Drosophila (88,89). In the following sections, we describe this type of hsc70-dependent eMI in the context of other types of microautophagy and in comparison, with CMA ( Figure 5).…”
Section: Endosomal Microautophagy 31 General Descriptionmentioning
confidence: 93%